2022
DOI: 10.1093/jpepsy/jsab139
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 Among Black Girls: A Social-Ecological Perspective

Abstract: Objective To explore the impact of the COVID-19 pandemic on Black adolescent girls’ physical, psychological, and sexual development. Methods Semistructured interviews were conducted with 25 girls (9–18 years old) primarily across the Midwestern United States. Interviews were conducted until theoretical saturation was reached. We conducted a conventional content analysis by reviewing transcripts, coding data, and developing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…The onset of the COVID-19 pandemic further exacerbated the issues Black girls experience in K-12 schools. For example, Black girls and their families were already vulnerable in the health care system due to anti-Black racism, and the addition of the COVID-19 pandemic meant that if exposed, they would be subjected to the cruelty of anti-Blackness that would render their symptoms and pain as an acceptable casualty (Crooks et al, 2022). In fact, the disproportionate death toll related to COVID-19 in the Black community has meant that Black girls and their families have experienced significant changes in family functioning marked with sustained grief.…”
Section: Impact Of Covid-19mentioning
confidence: 99%
See 2 more Smart Citations
“…The onset of the COVID-19 pandemic further exacerbated the issues Black girls experience in K-12 schools. For example, Black girls and their families were already vulnerable in the health care system due to anti-Black racism, and the addition of the COVID-19 pandemic meant that if exposed, they would be subjected to the cruelty of anti-Blackness that would render their symptoms and pain as an acceptable casualty (Crooks et al, 2022). In fact, the disproportionate death toll related to COVID-19 in the Black community has meant that Black girls and their families have experienced significant changes in family functioning marked with sustained grief.…”
Section: Impact Of Covid-19mentioning
confidence: 99%
“…In fact, the disproportionate death toll related to COVID-19 in the Black community has meant that Black girls and their families have experienced significant changes in family functioning marked with sustained grief. Essentially, Black girls have had to learn a new way of being and knowing to stay alive while also experiencing immense grief as their family structures changed rapidly due to death and dying (Crooks et al, 2022).…”
Section: Impact Of Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Adolescents who perceived higher levels of racism and discrimination during the COVID-19 pandemic, especially Asian, Black, and multiracial youths, reported poorer mental health outcomes and more difficulty concentrating, remembering, or making decisions [ 22 ]. Anti-Asian sentiments surrounding the origins of the virus and the highly publicized recordings of police brutality against Black individuals heightened youths’ anxiety, promoted feelings of othering, and fostered a reduced sense of belonging in these communities [ 19 , 23∗ , 24∗∗ , 25∗ , 26∗ ]. Ethnic-racial minority youths reported anger, frustration, and hopelessness because they lacked resources to enact change against the cyclical nature of racial violence [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…A qualitative study by Crooks et al. [ 24 ] found that Black youths reported increased media coverage surrounding these injustices, which caused racial tension, anxiety, and distress. Experiencing online racial discrimination affected Black youths’ mental health [ 31 ].…”
Section: Introductionmentioning
confidence: 99%